1987
DOI: 10.1128/jb.169.9.4041-4048.1987
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the structural gene for dipeptidyl aminopeptidase yscV (DAP2) of Saccharomyces cerevisiae

Abstract: Strain Genotype Source or reference MATa MATot stel3-1 ade6 leul trpS his6 met) can) rmel gal2 MATa sstl-2 ade2 ural his6 metl cyh2 rme MATa sst2-1 ade2 ural his6 met) cyh2 rme MATa pral-J prbl-l prcl-) cpsl-3 ade2 his MATot ste)3-1 prbl-l prcl-) cpsl-3 ade2 his MATot stel3-1 prbl-l prcl-l cpsl-3 ape2-1 leu2 his MATa prcl-l cpsl-3 ape2-1 leu2 MATa prcl-l cpsl-3 ape2-1 leu2 lys2 MATa stel3-1 dap2-1 prbl-l prcl-J cpsl-3 ape2-1 leu2 his MATa stel3-1 dap2-2 ade6 leul trpS his6 met) can) rmei gaI2 MATa stel3-1 dap2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…and 1 mM L-l-tosyl-2-phenylethyl chloromethane (TPCK). Proteins were extracted from the cell pellets using the equivalent of 200 p1 glass beads (75 -150 um)/0.2 g wet mass cells, following the method previously described (Rendueles and Wolf, 1987). The protein concentration of the cell extracts and supernatant was determined by the method of Bradford (1976).…”
Section: Cell Culture and Enzymatic Assaymentioning
confidence: 99%
“…and 1 mM L-l-tosyl-2-phenylethyl chloromethane (TPCK). Proteins were extracted from the cell pellets using the equivalent of 200 p1 glass beads (75 -150 um)/0.2 g wet mass cells, following the method previously described (Rendueles and Wolf, 1987). The protein concentration of the cell extracts and supernatant was determined by the method of Bradford (1976).…”
Section: Cell Culture and Enzymatic Assaymentioning
confidence: 99%
“…42 C. glabrata displayed proteolytic activity similar to that found in some other yeasts, including S. cerevisiae, Schizosaccharomyces pombe, Kluyveromyces lactis, and Yarrowia lipolytica. 9,10,24,37,38 Previous data revealed that the levels of PrA, PrB, and CpY proteases are dependent on the growth phase and composition of the nutrients in the growth media, e.g. higher levels of these proteases detected during early stationary phase in this study (data not shown).…”
Section: Discussionmentioning
confidence: 61%
“…These results suggest that these proteases might be regulated by the source of nitrogen and carbon, as occurs with other fungi. 9,10,37,38 Our findings based on the enzymatic activity of PrA, PrB and CpY proteases from the vacuolar fraction of C. glabrata displayed an increased activity suggesting their specific location in this organelle. The value of the enriched-activity yield for PrA is commensurate with the preparation of the pure vacuole as described in S. cerevisiae.…”
Section: Discussionmentioning
confidence: 80%
“…The stop codon of this gene is located only 46 bp from the stop codon of PIM1 in P. pastoris. DAP2 codes for a dipeptidyl aminopeptidase of 818 amino acids, and mutations in this gene do not cause any obvious phenotype under a variety of conditions tested (Sua rez Rendueles and Wolf 1987;Winzeler et al 1999). Therefore, a role for the P. pastoris Dap2 homologue in cell integrity is unlikely.…”
Section: Resultsmentioning
confidence: 99%